2012
DOI: 10.1002/macp.201100647
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive Composite Based on a Monolithic Polymer

Abstract: A new class of photorefractive (PR) composite based on a fully functionalized polymer with high phase-stability is reported. The polymer containing non-linear optical (NLO) chromophores and charge-transporting carbazole moieties is synthesized by a polymer-analogous reaction. The polymer is doped with plasticizer, NLO dye, and sensitizer to fabricate the PR composite. The NLO dye is the same as the NLO chromophore moiety in the polymer side chain. The PR performance of the composite is evaluated by degenerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Many methods that use a different chromophore or a mixture of different chromophores and a monolithic polymer have been developed. [20][21][22] A co-polymer containing triphenylamine and a small amount of the NLO chromophore in the polymer side chain will improve the compatibility between the matrix and the chromophore without reducing the polymer photoconductivity. Future work will focus on co-polymer synthesis to extend the shelf life while maintaining high PR performance.…”
Section: Resultsmentioning
confidence: 99%
“…Many methods that use a different chromophore or a mixture of different chromophores and a monolithic polymer have been developed. [20][21][22] A co-polymer containing triphenylamine and a small amount of the NLO chromophore in the polymer side chain will improve the compatibility between the matrix and the chromophore without reducing the polymer photoconductivity. Future work will focus on co-polymer synthesis to extend the shelf life while maintaining high PR performance.…”
Section: Resultsmentioning
confidence: 99%
“…The polymer precipitate was collected by a centrifugation (4000 rpm, 20 min) to yield PTAA as a pale yellow powder (95.1% yield, Mw: 22,000 g mol −1 , M w / M n : 1.8, T g : 60.7 °C). Piperidinodicyanostyrene (PDCST) as a nonlinear optical (NLO) dye and (2,4,6‐trimethylphenyl)diphenylamine (TAA) as a plasticizer were synthesized using procedures described in the literature . [6,6]‐Phenyl‐C61‐butyric acid methyl ester (PCBM) (Tokyo Kasei) was used as a sensitizer.…”
Section: Methodsmentioning
confidence: 99%
“…Organic photorefractive (PR) polymers have wide potential for updatable holographic imaging and dynamic holographic displays. Dynamic holography is the ultimate in three-dimensional (3D) imaging and is expected to be key technology for a next-generation display system. Photorefractive phenomena are based on refractive index modulation derived from the distributed space-charge field through the Pockels (first-order optical nonlinearity) effect. Since the first study of organic photorefractive polymers was reported, numerous research investigations have focused on PR polymers. , …”
Section: Introductionmentioning
confidence: 99%